The Mexican-American War - Rebman, Nick (Expansion of our nation., 2019)
Describes the expansion of the United States, focusing on the Mexican-American War. Discusses the addition of Texas, how President Polk led the nation into war, and the invasion and defeat of Mexico. Also details the aftermath of the war and the continuing issue of slavery. Includes a quiz with answer key, a glossary, color illustrations, and further resources.